The roots of modern psychology and law : a narrative history - Grisso, Thomas; Brodsky, Stanley L. (Oxford : Oxford University Press, 2018)
Psychology's formal interaction with law began early in the twentieth century, though little in the way of substantive scholarly and professional development occurred until several decades later. The emergence of psychology and law as a modern field of scholarship was marked by the founding of the American Psychology-Law Society (AP-LS) in 1969, now approaching its 50th anniversary. The scientific foundation upon which the modern field now rests was established by a small group of psychological researchers, legal scholars, and clinicians. The Roots of Modern Psychology and Law: A Narrative History reveals how the field developed during the first decade following the founding of the American Psychology-Law Society. The contributors to this edited volume, widely considered to be among the "founders" of the field, were responsible for establishing and nurturing many of the subfields and topics in psychology and law or forensic psychology that flourished across the next fifty years. In each chapter, these leaders explain in narrative form how and why the field and the Society developed in its early years through the recounting of key professional events in their careers during the 1970s. In some cases this was their first major research study using psychology applied to legal issues. In others it was their development of seminal ideas or organizational innovations that had a later impact on the field's development. The volume chronicles how an emerging AP-LS and field of psychology and law were shaped by these psychologists, and how their own initial work was, in turn, shaped by the organization
Section II Assessment, Interventions, and Practice in Legal Contextsâ#x80;#x82;8. Forensic Mental Health Services and Competence to Stand Trial; â#x80;#x82;9. Predictions of Violence; 10. Developmental Psycholegal Capacities; 11. Correctional Psychology; 12. The Founding and Early Years of the American Board of Forensic Psychology; 13. Community Psychology, Public Policy, and Children; Editorsâ#x80;#x99; Epilogue; Index
Includes bibliographical references and index.
Vendor-supplied metadata.
eBooks on EBSCOhost
Keywords: Law -- Psychological aspects; Forensic psychology; Droit -- Aspect psychologique; Psychologie légale.; LAW -- Essays; LAW -- General Practice; LAW -- Jurisprudence; LAW -- Paralegals & Paralegalism; LAW -- Practical Guides; LAW -- Reference; Forensic psychology; Law -- Psychological aspects; Law